Suočavanje s prošlošću u online medijima u Bosni i Hercegovini / Dealing with the Past in Online Media in Bosnia and Herzegovina - Delić, Amela (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
The aim of this article is the analysis of the importance of the media in the process of facing the past, overcoming cultural trauma that exists in the area after conflicts and their symbolic representation. First, it examines the role of traditional media in spreading the atmosphere of fear and intolerance before disintegration of Yugoslavia, and then the way in which the new media deals with the shadows of the past. The questions on which there is the most disagreement, regarding the past conflicts in Bosnia and Herzegovina, are analyzed. Who are the perpetrators and the victims of the last war? What is the role of media in conveying the competing visions of the past? Is a struggle for media actually struggle for the control of the meaning of the past? The survey to find the answers to these questions was conducted throughout six-month period and it includes the analysis of twelve web portals in Bosnia and Herzegovina. It is analyzed how the media refers to the past, and how relevant, systematic and responsible way of dealing with topics of traumatic period is. The conclusion is that the topics related to traumatic war events are presented in the media in the same way as other daily political news. The key advantage of the Internet over traditional media, which is reflected in interactivity, has not yet been accepted in BiH society which still prefers to communicate without feedback, insensitive to the needs and opinions of others. In total of 3441 (7.011%) news related to the war on twelve websites in the period of six months, only 46 (0.095%) of them were related to the importance of dealing with the past and reconciliation. The World Wide Web has created tremendous opportunities for improving communication, but deciding factor for development is still social, economic and cultural context in which the media exists.